FRANZ KAFKA'S MESSAGE OF PASSIVE NIHILISM IN THE NOVEL METAMORPHOSIS - Al Husaini, Wafiiq Majdiy; Sumayah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study explores how Friedrich Nietzsche's concept of passive nihilism is reflected in Franz Kafka's novella The Metamorphosis, while examining its intimate connection to the author's own life experiences. Using a descriptive qualitative design grounded in Gadamerian hermeneutics, textual elements—such as dialogues and narrative units—were critically interpreted alongside philosophical literature and biographical sources. The findings reveal that Gregor Samsa's existential decline manifests through five key dimensions: mental exhaustion and dwindling vitality, profound apathy, the erosion of personal values, escapism, and blind obedience to external demands. Samsa's tragic collapse closely echoes Kafka's personal struggles under an overbearing paternal figure and a stifling corporate routine. Ultimately, through this absurd tale of transformation, Kafka offers more than a portrayal of helplessness; he delivers a subtle yet powerful critique of modern structures that strip the individuals of their humanity, urging readers to preserve their autonomy and inner freedom.